2020
DOI: 10.1002/jhbp.784
|View full text |Cite
|
Sign up to set email alerts
|

Level of total bilirubin in the bile of the future remnant liver of patients with obstructive jaundice undergoing hepatectomy predicts postoperative liver failure

Abstract: Background We investigated whether the daily level of total bilirubin in the bile (LTB) excreted from the future remnant liver (FRL) can predict post‐hepatectomy liver failure (PHLF) in patients with obstructive jaundice undergoing hepatectomy. Methods Seventy‐four patients who underwent biliary drainage and collection of bile juice from the FRL before undergoing right hepatectomy or right/left trisectionectomy with bile duct resection were included. The LTB from the FRL (mg/d) was calculated as the volume of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Studies have shown that elevated transaminases and serum bilirubin may present with obstructive jaundice when the left and right hepatic ducts are obstructed at the same time or the common hepatic duct is obstructed, and patients may present with only elevated transaminases and normal serum total bilirubin when one hepatic duct is obstructed alone [ 18 ]. The detection results showed that serum AST, ALT, TBIL, Na + , and K + contents in the control group were 118.4 ± 6.2 U/L, 55.7 ± 1.2 U/L, 1.9 ± 0.4 μ mol/L, 135.74 ± 4.76 mmol/L, and 4.14 ± 0.52 mmol/L, respectively; the serum AST content in the study group before treatment was 146.3 ± 9.7 U/L, significantly higher than that in the control group, and the difference had a statistical significance ( P < 0.05); after treatment, the serum AST content was 123.5 ± 4.9 U/L, significantly lower than that before treatment, and the difference had statistical significance ( P < 0.05); the TBIL content was 1.8 ± 0.3 μ mol/L, significantly lower than 2.2 ± 0.5 μ mol/L before treatment, and the difference had statistical significance ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that elevated transaminases and serum bilirubin may present with obstructive jaundice when the left and right hepatic ducts are obstructed at the same time or the common hepatic duct is obstructed, and patients may present with only elevated transaminases and normal serum total bilirubin when one hepatic duct is obstructed alone [ 18 ]. The detection results showed that serum AST, ALT, TBIL, Na + , and K + contents in the control group were 118.4 ± 6.2 U/L, 55.7 ± 1.2 U/L, 1.9 ± 0.4 μ mol/L, 135.74 ± 4.76 mmol/L, and 4.14 ± 0.52 mmol/L, respectively; the serum AST content in the study group before treatment was 146.3 ± 9.7 U/L, significantly higher than that in the control group, and the difference had a statistical significance ( P < 0.05); after treatment, the serum AST content was 123.5 ± 4.9 U/L, significantly lower than that before treatment, and the difference had statistical significance ( P < 0.05); the TBIL content was 1.8 ± 0.3 μ mol/L, significantly lower than 2.2 ± 0.5 μ mol/L before treatment, and the difference had statistical significance ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The chemiluminescence (ChL) method allows the analysis of the features of a respiratory burst in spontaneous and induced states in various diseases 14 . An extremely important indicator for patients with MJ is their bilirubin level, which plays a crucial role in the disease progression 15 . It has been previously shown that the increased levels of serum bilirubin may be the reason for the bactericidal activity of neutrophils' impairment in patients with hyperbilirubinemia 16,17 .…”
Section: Introductionmentioning
confidence: 99%